Приближенные граничные условия и коэффициенты экранирования тонких проводящих оболочек - Бондина, Н.Н.; Живанков, К.И.; Михайлов, В.М. (Технічна електродинаміка, 2012)
Boundary conditions for tangential components of electromagnetic field strengths on thin conductive layer surfaces are obtained depending on current distribution approximation in thickness of it. Uniform, linear and plane wave current distribution approximations are considerated. The errors of the approximations are estimated by way of calculation of spherical and cylindrical screen coefficients.